(untitled) (Journal of Scientific Research, 2024)
Iron oxide magnetic nanoparticles (MNP) are considered to be emergent nanoparticles for magnetic separation and MRI imaging probes. Here, glucose-functionalized iron oxide (γ-Fe2O3) magnetic nanoparticles have been prepared for specific protein detection and separation. First, hydrophobic iron oxide (γ-Fe2O3) was synthesized by standard organometallic approaches, and the same has been converted to soluble, colloidally stable, hydrophilic primary amine (-NH2)-PEG terminated iron oxide (γ-Fe2O3) nanoparticles using reverse micelle based robust polyacrylate coating chemistry. Then, glucose was covalently linked to this amine (-NH2)-PEG terminated iron oxide (γ-Fe2O3) nanoparticles by using glutaraldehyde-based coupling chemistry. Finally, glucose-functionalized iron oxide (γ-Fe2O3) nanoparticles have been used for specific detection and separation of a glycoprotein, Concanavalin-A.